(untitled) (Sains Humanika, 2019)
A Learning Object Repository (LOR) is a concept of storage, reuse and sharing of learning objects accompanied by the community in the education sector consists of students and educators. One of the elements identified to distinguish the quality of a learning object repository is the interface usability. Usability is critical for the success of an application to help users achieve their objectives. Based on previous studies, very few researches have been conducted to highlight problems in the usability of LORs. In addition, the current LOR interfaces did not help facilitate users to achieve the objectives of their assignments. Hence, a comprehensive heuristic study on interface usability was conducted on three chosen LORs in order to identify the basic functions that must exist in the LOR interface, to develop an interface prototype to be used as a model reflecting the heuristic results, and to perform tests on the interface prototype developed. The methodology of this study involves three phases: planning, execution, and development. In the execution phase, the severity ratings for the LOR interfaces were identified by Nielsen Evaluation. The prototype was tested to ensure that the usability principles were adhered.